Intracerebral Hemorrhage: Perihemorrhagic Edema and Secondary Hematoma Expansion: From Bench Work to Ongoing Controversies - Mittal, Manoj K.; LacKamp, Aaron (Frontiers in Neurology, 2016)
Intracerebral hemorrhage (ICH) is a medical emergency which often leads to severe disability and death. ICH-related poor outcomes are due to primary injury causing structural damage and mass effect and secondary injury in the peri-hemorrhagic region over several days to weeks. Secondary injury after ICH can be due to hematoma expansion (HE) or a consequence of repair pathway along the continuum of neuroinflammation, neuronal death, and peri-hemorrhagic edema (PHE). This review article is focused on PHE and HE and will cover the animal studies, related human studies, and clinical trials relating to these mechanisms of secondary brain injury in ICH patients.